2023
DOI: 10.3390/pathogens12050667
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus (HEV) Infection in Hemodialysis Patients: A Multicenter Epidemiological Cohort Study in North-Eastern Greece

Abstract: Hepatitis E virus (HEV), a common cause of viral hepatitis in developing countries, is mainly transmitted via the fecal–oral route, but also may be a prevalent hospital-transmitted agent among patients on regular hemodialysis due to parenteral transmission. Previous epidemiological studies among hemodialysis patients in Greece, using different diagnostic techniques, gave conflicting results. Τhe present study aimed to measure the exposure rate of hemodialysis patients of north-eastern Greece to HEV by estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
3
1
Order By: Relevance
“…The observed rise in the proportion of HEV-positive HD patients with increasing age, although not statistically significant (Figure 2), has been similarly documented in other research centers [6,41,42,47]. This phenomenon can be partially attributed to the tendency of dialysis research to primarily focus on the adult population (≥18 years old), rather than encompassing the entire age range typically observed in population studies.…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…The observed rise in the proportion of HEV-positive HD patients with increasing age, although not statistically significant (Figure 2), has been similarly documented in other research centers [6,41,42,47]. This phenomenon can be partially attributed to the tendency of dialysis research to primarily focus on the adult population (≥18 years old), rather than encompassing the entire age range typically observed in population studies.…”
Section: Discussionsupporting
confidence: 67%
“…This assertion is substantiated by the authors' previous findings, which indicated a seroprevalence rate of 65.1% among individuals who were not undergoing hemodialysis. Prior studies undertaken in Greece at different time periods have shown significant discrepancies among dialysis centers across various locations of the nation [6,22]. Nevertheless, the findings of our study did not reveal any significant variations, as seen by the data presented in Table 2.…”
Section: Discussioncontrasting
confidence: 48%
See 3 more Smart Citations